Sanctions for Rejection of Covid-19 Vaccines seen from the Perspective of the Human Rights Act and the Health Quarantine Act: Sanksi Penolakan Vaksin Covid-19 dilihat dari Perspektif Undang-Undang Hak Asasi Manusia(HAM) dan Undang-Undang Kekarantinaan Kesehatan - Mawa, Damai Yanti Zulfatal; Mediawati, Noor Fatimah; Phahlevy, Rifqi Ridlo; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2022)
Presidential Regulation Number 99 of 2020 concerning Vaccine Procurement and Vaccination Implementation in the Context of Combating the 2019 Corona Virus Disease (COVID-19) Pandemic. The method used is normative using a statute approach, which is carried out by reviewing all laws and regulations related to this research. Collecting data from this study through primary legal materials consisting of legislation, official records or minutes in the making of legislation and judges’ decisions. Meanwhile, secondary legal materials are in the form of textbooks, legal dictionaries, legal journals, and comments on court decisions. Is the refusal of a Covid-19 vaccine a violation of human rights law? And is refusing the Covid-19 vaccine a violation of the Health Quarantine Act? From this study, it can be concluded that the application of sanctions for the rejection of the COVID-19 vaccine is a form of legal protection for the community, as a form of effort to prevent the spread of the corona virus. Where the government has an obligation to protect the public from the risk of transmission of the covid-19 disease outbreak. Keywords - rejection sanctions, covid-19 vaccine, protection.